Leukocyte Activation Profile Assessed by Raman Spectroscopy Helps Diagnosing Infection and Sepsis. (12th May 2021) - Ramoji, Anuradha; Thomas-Rüddel, Daniel; Ryabchykov, Oleg; Bauer, Michael; Arend, Natalie; Giamarellos-Bourboulis, Evangelos J.; Eugen-Olsen, Jesper; Kiehntopf, Michael; Bocklitz, Thomas; Popp, Jürgen; Bloos, Frank; Neugebauer, Ute
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Leukocytes are first responders to infection. Their activation state can reveal information about specific host immune response and identify dysregulation in sepsis. This study aims to use the Raman spectroscopic fingerprints of blood-derived leukocytes to differentiate inflammation, infection, and sepsis in hospitalized patients. Diagnostic sensitivity and specificity shall demonstrate the added value of the direct characterization of leukocyte's phenotype. Design: Prospective nonrandomized, single-center, observational phase-II study (DRKS00006265). Setting: Jena University Hospital, Germany. Patients: Sixty-one hospitalized patients (19 with sterile inflammation, 23 with infection without organ dysfunction, 18 with sepsis according to Sepsis-3 definition). Interventions: None (blood withdrawal). Measurements AND MAIN RESULTS: Individual peripheral blood leukocytes were characterized by Raman spectroscopy. Reference diagnostics included established clinical scores, blood count, and biomarkers (C-reactive protein, procalcitonin and interleukin-6). Binary classification models using Raman data were able to distinguish patients with infection from patients without infection, as well as sepsis patients from patients without sepsis, with accuracies achieved with established biomarkers. Compared with biomarker information alone, an increase of 10% (to 93%) accuracy for the detection of infection and an increase of 18% (to 92%) for detection of sepsis were reached by adding the Raman information. Leukocytes from sepsis patients showed different Raman spectral features in comparison to the patients with infection that point to the special immune phenotype of sepsis patients. Conclusions: Raman spectroscopy can extract information on leukocyte's activation state in a nondestructive, label-free manner to differentiate sterile inflammation, infection, and sepsis.